Prevalence of Anemia and Associated Risk Factors among Pregnant Women Attending Antenatal Care Clinic at Katihar Medical College & Hospital, Bihar - Kumari, Seema; Bharati, Dharmvir Ranjan; Jayaswal, ANil Kumar; Pal, Ranbir; Sinha, Shivani; Kumari, Anju (National Journal of Community Medicine, 2017)
Background: In India anaemia continue to be high (88.5%) and is the second most common cause of maternal deaths, accounting for almost one-fifths of total maternal deaths. Objectives: The present study was undertaken to find the prevalence of undiagnosed anemia among pregnant women and its socio-demographic correlates. Methods: It was a hospital based cross-sectional study, conducted among 400 pregnant women attending their first time antenatal visit at the outpatient department of Obstetrics and Gynecology of Katihar Medical College and Hospital. Results: Out of 400 pregnant women 88.5 percent were found to be anaemic; maximum in the age group of less than 18 years. Anemia was significantly associated with age, parity, gestational age and inversely related to religion, birth interval, type of the family, socioeconomic and educational status, calories and protein intake. Conclusions: The prevalence of undiagnosed anemia among pregnant women was quite high and were associated with age, parity, gestational age, birth interval, diet, socioeconomic and educational status.